KINERJA GURU DALAM MENINGKATKAN MUTU PENDIDIKAN MADRASAH - Fiandi, Arif; Junaidi, Junaidi (Jurnal Kepemimpinan dan Pengurusan Sekolah, 2022)
This study aims to examine the performance of teachers in improving the quality of madrasa education. The research method used is the library research method by collecting data and information from references and literature. The results of this study indicate that teachers are one of the main factors influencing the quality of education in madrasas. The quality of education is influenced by the performance of teachers. Teacher performance is the ability of teachers to carry out their main tasks, namely: designing learning program plans, implementing learning activity programs and evaluating learning. In order for teacher performance to be maintained and always increase, teacher performance assessment is also necessary. The higher the teacher's performance, the higher the quality of education in the madrasa.